Pelestarian Tari Piriang Rantak Tapi Di Kenagarian Pitalah Kecamatan Batipuh Kabupaten Tanah Datar - Srirahayu Srirahayu; Desfiarni Desfiarni (SENDRATASIK UNP, 2021)
This research aims to reveal and describe "The preservation of Piriang Rantak Tapi dance in Pitalah village, Batipuh District, Tanah Datar Regency". This research belongs to a qualitative research using descriptive method. The main instrument in this study was the researcher itself and was assisted by supporting instruments such as writing tools and cameras. The data were collected through literature study, observation, interview, and documentation. The steps of analyzing data were collecting the data, describing the data, and concluding the data. The results show that the effort to preserve the Piriang Rantak Tapi dance isby collaborating with the Tuo Tari and the community in Pitalah village, Batipuh district. With the training of Piriang Rantak Tapi dance, the number of performers has increased from 1 to 8 people in the dance, so that currently the RantakTapipiriang dance has had the next generation to maintain the existence of the dance. This has a positive impact and can be accepted by the community because there are many dance performers around the community. The impact learned in the PiriangRantak dance is that those who previously did not understand dance, but then they can dance a dance taught, namely Piriang Rantak Tapi Dance.